Negative and positive impacts of alien macrofungi: a global scale database - Monteiro, Miguel (2023)
Advances in ecological research during the last decades have led to an improved understanding of the impacts of alien species. Despite that, the effects of alien macrofungi have often received little attention and are still poorly understood. With the aim of reducing this knowledge gap, we compiled a database of the recorded socio-economic and environmental impacts of alien macrofungi. This database was compiled from all relevant sources we could identify, through an exhaustive literature review, considering the identity of known alien taxa and explicit indications of impacts of any kind. In total, 1440 records of both negative and positive impacts were collected for 374 distinct species in different regions of all continents, except Antarctica. The most frequently recorded impacts are related to the mutualistic interactions that these fungi can form with their host plants. In total 47.8% of all records refer to the indirect negative effect of these interactions, by facilitating the colonization of invasive plants, while 38.5% refer to their positive contribution to the growth of forestry species. Less frequently recorded negative impacts included ectomycorrhizal interactions with native plants, plant pathogenicity and human poisoning after ingestion. Additional positive impacts include the use as a food source by native species and human populations and commercial exploitation. Alien macrofungi are an increasingly prevalent component of human- dominated ecosystems, having a diverse array of negative and positive impacts on native biota and human population. Our database provided a first step towards the quantification and mapping of these impacts.